2004
DOI: 10.1111/j.1469-7610.2004.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, social cognitions, anger and sadness in bullies and victims

Abstract: Bullies and victims seem to be similar in reactive aggression, SIP, and in the expression of anger, but the motivations which lead to their behavior may be different, as well as the final outcomes of their acts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
235
4
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(276 citation statements)
references
References 75 publications
23
235
4
14
Order By: Relevance
“…The majority of this contribution is due to social competence, with higher social competence predicting more bullying in the 13-and 15-year-old cohorts. Contrary to recent studies (Andreou, 2004;Camodeca & Goossens, 2005), no significant effects were found for self-efficacy.…”
Section: Descriptive Statisticscontrasting
confidence: 54%
See 1 more Smart Citation
“…The majority of this contribution is due to social competence, with higher social competence predicting more bullying in the 13-and 15-year-old cohorts. Contrary to recent studies (Andreou, 2004;Camodeca & Goossens, 2005), no significant effects were found for self-efficacy.…”
Section: Descriptive Statisticscontrasting
confidence: 54%
“…Although the concept of power has been central to defining bullying, and bullies have been found to be higher in self-efficacy, at least in aggressive contexts (Andreou, 2004;Camodeca & Goossens, 2005), little is known about the dynamics of the power differential. For example, it is not clear how or why the bully-victim power differential develops, whether the power differential is unique to the bully-victim dyad, or is generalized in bullies' and victims' relationships to other friends, family and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, over 100 studies have documented this phenomenon in aggressive youth and adults from a wide variety of populations, and a meta-analysis (de Castro, Veerman, Koops, Bosch, & Monshouwer, 2002) has revealed a robust phenomenon with a strong mean effect size. In community populations, the finding has been reported among: rejected-aggressive elementary school boys (Guerra & Slaby, 1989;Lochman, 1987;Sancilio, Plumert, & Hartup, 1989;Waas, 1988), and girls (Feldman & Dodge, 1987), European American aggressive children (Dell Fitzgerald & Asher, 1987), African American children (Graham & Hudley, 1994), Latino children (Graham, Hudley, & Williams, 1992), Dutch children (Comodeca & Goossens, 2004), and aggressive junior high school youth (Dodge & Tomlin, 1987).…”
Section: Hostile Attributional Bias and Aggressive Behaviormentioning
confidence: 87%
“…Moreover, children involved in bullying exhibit differential types of aggression (eg, reactive versus proactive) depending on the situation and whether they are mainly bullies, victims, or bully-victims. 50 Our measures did not capture children's perceptions of peer intentions or ascertain specifics on the circumstances surrounding bullying incidents or whether there were any triggers. Given that we found an association between IPV and parent-reported externalizing and internalizing child behaviors similar to past studies, the systematic measurement of bullying may be problematic, especially in those who come from violent homes.…”
Section: Discussionmentioning
confidence: 99%